MgO-based catalysts for monoglyceride synthesis from methyl oleate and glycerol: Effect of Li promotion - Ferretti, Cristián Alejandro (2011)
The synthesis of monoglycerides (glyceryl monooleates) by heterogeneously catalyzed glycerolysis of an unsaturated fatty acid methyl ester (methyl oleate) was studied on MgO and Li-promoted MgO catalysts. Several MgO-based catalysts with different Li loadings were prepared by incipient wetness impregnation and characterized by XRD, N2 physisorption, and FTIR and TPD of CO 2 among other techniques. Promotion of MgO with lithium, a basic promoter, affected the textural and structural properties of the resulting oxides so that more crystalline MgO phases with decreased surface area were obtained at increasing Li contents. Furthermore, the addition of Li generated new strong base sites because of formation of dispersed surface Li2O species, and thereby increased the total base site density of parent MgO. Li-containing MgO catalysts efficiently promoted the glycerolysis reaction, achieving high monoglyceride yields (70-73%) at 493 K. The initial monoglyceride formation rate increased linearly with the Li content on the sample following the enhanced overall catalyst base strength. Although conversions at the end of the run were ≈100% for all the catalysts, the monoglyceride selectivity slightly decreased with the Li loading, probably as a consequence of the less surface affinity for glycerol adsorption that facilitates competing monoglyceride re-adsorption and transformation to diglycerides by consecutive glycerolysis or disproportionation reactions.